Manajemen Pembelajaran Iqro Untuk Membina Kemampuan Baca Tulis Al-Qur’an Siswa Kelas I MI - Andri Marta Sudirja Andri; Asep Ahmad Ridwansyah Asep (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
The Al-Qur'an learning method is essentially teaching the Al-Qur'an to children, which is a process of introducing the Al-Qur'an to the first stage with the aim of making students recognize letters as sound signs or sound signs. The most important thing in learning to read the Al-Qur'an is the skill of reading the Al-Qur'an well in accordance with the rules laid down in the science of Tajwid. The low motivation of students in learning the Al-Qur'an is still one of the causes of the low quality of education, especially in the ability to read the Al-Qur'an. One effort to increase motivation to learn to read and write the Al-Qur'an is by using appropriate methods that can be used by teachers to read and write the Al-Qur'an in the classroom. In educating religious students at elementary school level, a certain approach is needed, including through a religious approach. The religious approach is how educators process students through guidance, training and religious teaching activities, including directing, encouraging and encouraging them to want to learn the teachings of their religion through reading and writing the Qur'an. This research aims to identify Iqro learning management to develop the ability to read and write the Al-Qur'an for class I MI students.